Bell Jar - Plath, Sylvia 1932-1963 (New York Harper & Row, 1971)
"A biography of writer Sylvia Plath that describes her era, her major works--the novel The bell jar and her poetry--her life, and the legacy of her writing"--Provided by publisher
37365
Keywords: Poets, American; Women Biography